Species of Mayan Cichlid (Cichlasoma urophthalmus) in the Tanjungan Water Pump Area, Jakarta - Dadiono, Muh Sulaiman (Journal of Aquaculture Development and Environment, 2023)
The foreign predatory fish Mayan cichlid (Cichlasoma urophthalmus) in the waters causes a reduction in biodiversity and is very dangerous for the sustainability of the aquatic ecosystem in Indonesia. This study aims to analyze and describe the catch of the mayan cichlid and examine the negative impact of finding this species in the Tanjungan Water Pump Jakarta. This study used the desk study method, observations by informants in the field and species identification methods based on morphological observations of Miller et al. (2005) and Nico et al. (2007). The finding of the Mayan cichlid fish species in the Tanjungan Water Pump Jakarta is an alarm or sign of the negative impacts of invasive fish to the government so that they can develop regulations that are focused and directed towards the spread of invasive species in Indonesian.